Early aggressive intervention for infantile atopic dermatitis to prevent development of food allergy: a multicenter, investigator‐blinded, randomized, parallel group controlled trial (PACI Study)—protocol for a randomized controlled trial. Issue 1 (23rd November 2018) - Yamamoto‐Hanada, Kiwako; Kobayashi, Tohru; Williams, Hywel C.; Mikami, Masashi; Saito‐Abe, Mayako; Morita, Kumiko; Natsume, Osamu; Sato, Miori; Iwama, Motoko; Miyaji, Yumiko; Miyata, Makiko; Inagaki, Shinichiro; et al.
Abstract: Background: Atopic dermatitis is the first clinical manifestation of the atopic march, with the highest incidence in the first year of life. Those affected often go on to develop other allergic diseases including food allergy, asthma, and allergic rhinitis. Recent evidence suggests that sensitization to foods may occur through a defective skin barrier which is common in atopic dermatitis in early life. We hypothesize that therapeutic aggressive intervention to treat new onset atopic dermatitis may prevent the development of later allergen sensitization, and associated food allergy, asthma, and allergic rhinitis. Methods: This study is a multi‐center, pragmatic, two‐parallel group, assessor‐blind, superiority, individually randomized controlled trial. Atopic dermatitis infants (N = 650) 7–13 weeks old who develop an itchy rash within the previous 28 days are randomly assigned to the aggressive treatment or the conventional treatment in a 1:1 ratio. The primary outcome is oral food challenge‐proven IgE‐mediated hen's egg allergy at the age of 28 weeks. Discussion: This is a novel pragmatic RCT study to examine the efficacy of early aggressive treatment for atopic dermatitis to prevent later food allergy. If our hypothesis is correct, we hope that such a strategy might impact on disease prevention in countries where food allergy is common, and that our results might reduce the frequency and associated costs of all food allergies as well as hens egg food allergy. Long‐term follow and other similar studies will help to determine whether such a strategy will reduce the burden of other allergic diseases such as asthma and allergic rhinitis. Trial registration UMIN‐CTR: UMIN000028043